Direct Exfoliation of Graphite to Graphene by a Facile Chemical Approach. Issue 11 (7th March 2014) - Feng, Hongbin; Wu, Yongmin; Li, Jinghong
<x xml:space="preserve">Abstract</x> Facile exfoliation of graphite: High‐quality graphene sheets are produced directly from graphite by a facile chemical approach. The new strategy for non‐oxidized chemical exfoliation of graphite is based on a pre‐intercalated process with oleum and a further strong reaction with sodium in the graphite layers under grinding conditions. This method is facile, low cost, and high throughput. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>